Work-Life Balance and Employee Productivity: The Mediating Role of Job Satisfaction Among Generation Z - Muhammad Syafri; Mhd. Andi Rasyid (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze the effect of work-life balance on employee productivity, with job satisfaction serving as a mediating variable among Generation Z employees. The research employed a quantitative approach using a survey method involving 150 Generation Z employees in Medan City. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 4 software. The results indicate that work-life balance has a positive and significant effect on both job satisfaction and employee productivity. Job satisfaction also has a positive effect on productivity and is proven to partially mediate the relationship between work-life balance and employee productivity. These findings highlight the importance of organizational policies that support work-life balance in enhancing both job satisfaction and productivity among Generation Z employees.